Residual flexural tensile strength of normal-weight and lightweight steel fibre-reinforced concrete at elevated temperatures - Gondokusumo, Gilbert Sebastiano; Venkateshwaran, Akshay; Li, Shan; Liew, J.Y. Richard (Construction & building materials, 2023)
•A study was conducted on the residual flexural tensile strength of steel fibre reinforced concrete at elevated temperatures.•The flexural tensile strength retention of SFRC exhibited reduces with increase of temperature following a bilinear law.•Simplified equations are proposed to predict SFRC residual flexural tensile strength at elevated temperatures within 98% accuracy when compared to test results. In this study, the residual flexural tensile strength (fR,j) of steel fibre reinforced concrete (SFRC) at elevated temperature was investigated through a detailed test program. Sixty pre-notched SFRC prism specimens, cast with both normal-weight and lightweight concrete with different fibre contents, were heated inside a furnace to temperature ranging from 200 °C to 800 °C. The uniformly heated specimens were then subject to three-point bending using a carefully configurated test setup, to evaluate the residual flexural tensile strengths at elevated temperatures. The specimens were also tested at ambient temperature for benchmark comparison. A drop in both the residual flexural tensile strengths and the stiffness of SFRC was observed with the increase of temperature. The flexural tensile strength retention plotted against the elevated temperature exhibited a bilinear relationship. Based on the experimental results, a piecewise linear regression analysis was carried out to propose empirical equations to predict the residual flexural tensile strength of SFRC at elevated temperatures. The proposed equations were able to predict the strength retention factors with an average accuracy of around 98 % and a standard deviation of 18 % on average. The results from this study form the basis for predicting the behaviour of SFRC structural members under fire conditions.